THE EFFECT OF WAYANG MEDIA ON FOLKLORE LISTENING SKILLS - Fera Fazriani Nurafifah; Marlina Eliyanti Simbolon; Mia Noviana (Indonesian Journal of Elementary Teachers Education, 2021)
The aim of this study is to describe the difference in the results of the pre-test and post-test of the experimental class using wayang media with the control class without using learning media as well as describing the increase in the ability to listen to folklore in Indonesian subjects in class V SDN 1 Windusengkahan. The method used is quasi eksperiment with the experimental class using wayang media and the control class without using learning media. Data collection techniques are test and documentation.This learning process uses the Non-Equivalent Groups Pretest-Posttest design. This research was implemented on 20 students in the control class and 20 students in the experimental class. The conclusion of the research results are based on the differences folklore listening skills in Indonesian subjects between classes that use wayang media and classes that do not use learning media after treatment (posttest) and an increase (gain) folklore listening skills in Indonesian subjects between classes that do not use media Classroom learning using wayang media. Keywords: Puppet Media, Listening Skills, Folklore